Diferenciação de células tronco mesenquimais do tecido adiposo de ratas sob efeito da lactação e da prolactina - Karina Pessoa Oliveira (2017)
Two different experiments were performed. Experiment 1 evaluated the effect of lactation on the osteogenic differentiation of rats adipose derived-mesenchymal stem cells (ADSCs). Experiment 2 evaluated the osteogenic differentiation of ADSCs under the effect of two concentrations of prolactin. In experiment 1, ten Wistar rats were divided into two groups: 1) control, and 2) lactating. At 30 days of lactation, both groups were euthanized and samples of visceral adipose tissue were collected for ADSC extraction. ADSC was grown in osteogenic medium for 7, 14 and 21 days. The tests of MTT conversion into formazan crystals, alkaline phosphatase activity, collagen synthesis, percentage of mineralized nodules and cells per field and quantification of genic transcript for alkaline phosphatase, osteopontin, osteocalcin, bone sialoprotein, BMP-2, and collagen I by RT-PCR real time were made. The means were compared by the SNK test and the differences were considered significant if p <0.05. The lactating group had an increase in the conversion of MTT into formazan crystals at 7, 14 and 21 days. Alkaline phosphatase activity and collagen synthesis in the lactating group were greater only at 14 days. The lactation group had a higher percentage of mineralization nodules than control group, and a decrease in the percentage of cells. Lactation promoted increased in osteopontin expression at all times, bone sialoprotein at 7 and 21 days and BPM-2 only at 21 days. However, lactation reduced the expression of osteocalcin in all periods. It is concluded that the cells of lactating rats presented a greater osteogenic potential characterized by an increase of the mineralized matrix synthesis. In the experiment 2, ADSCs were grown in a medium with and without the addition of prolactin and distributed into three groups: 1) CTM-TA (control), 2) CTM-TA with addition of 100ng/mL prolactin, and 3) CTM-TA with addition of 300ng/mL prolactin. At 21 days of differentiation, the tests of MTT conversion into formazan crystals, percentage of mineralized nodules and cells per field and quantification of genic transcript for alkaline phosphatase, osteopontin, osteocalcin, bone sialoprotein, BMP-2, and collagen I by RT-PCR real time were made. The addition of prolactin reduced the conversion of MTT in group 3 and increased the percentage of cells/field in the groups 2 and 3, however without significantly increasing the percentage of nodules of mineralization and the expression of the genic transcription for for alkaline phosphatase, osteopontin, osteocalcin, bone sialoprotein, BMP-2, and collagen I. It is concluded that the addition of prolactin in concentrations of 100ng/mL and 300ng/mL does not change the osteogenic differentiation to the CTM-TA of female rats despite of increasing the cellularity of the culture.